The ecology of medical care in Norway: wide use of general practitioners may not necessarily keep patients out of hospitals - Anne Helen Hansen; Peder A. Halvorsen; Olav Helge Førde (SAGE Publishing, 2012)
Background. Our aim was to investigate the pattern of self reported symptoms and utilisation of health care services in Norway. Design and methods. With data from the cross-sectional Tromsø Study (2007-8), we estimated population proportions reporting symptoms and use of seven different health services. By logistic regression we estimated differences according to age and gender. Results. 12,982 persons aged 30-87 years participated, 65.7% of those invited. More than 900/1000 reported symptoms or health problems in a year as well as in a month, and 214/1000 and 816/1000 visited a general practitioner once or more in a month and a year, respectively. The corresponding figures were 91/1000 and 421/1000 for specialist outpatient visits, and 14/1000 and 116/1000 for hospitalisations. Physiotherapists were visited by 210/1000, chiropractors by 76/1000, complementary and alternative medical providers by 127/1000, and dentists by 692/1000 in a year. Women used most health care services more than men, but genders used hospitalisations and chiropractors equally. Utilisation of all services increased with age, except chiropractors, dentists and complementary and alternative medical providers. Conclusions. Almost the entire population reported health related problems during the previous year, and most residents visited a general practitioner. Yet there were high rates of inpatient and outpatient specialist utilisation. We suggest that wide use of general practitioners may not necessarily keep patients out of specialist care and hospitals.